Practical Significance of Early Diagnosis of Kidney Damage in Children - Dilmuradova, Klara (International Journal of Pediatrics and Child Health, 2023)
The authors present the results of follow-up observations of children that had undergone neonatal nephropathy. A follow-up observation revealed newborns from mothers with chronic kidney diseases are at risk for the development of neonatal nephropathies. The long-term positive results of the examination of children who underwent neonatal nephropathy and received a course of anti-relapse treatment proved the effectiveness of renal protection.